Appraisal of Provision of Guidance and Counselling to Postgraduate Distance Learners in Open University X, Malaysia - Marzo, Roy Rillera; Bhattacharya, Sudip (International Journal of Psychosocial Rehabilitation, 2020)
Background: One of the most important learner support services that can be provided to distance learners is guidance and counselling. This allowsthemtocope with their cognitive, psychological, and social needs while studying. Such servicescan bridge the gap between the institution and the student,asit acts tocompensate for the isolated “individual” and theabsence of “live support” from the teacher. Objective: The aim of the study is to establish how guidance and counselling services meet the needs of postgraduate distance learners in Open University X, Regional Centre, Malaysia. Methods: A descriptive cross-sectional study was employed among postgraduate distance learners in Open University • Data werecollected throughquestionnaires that aim to appraise the provision of guidance and counselling among the respondents. The survey instrument was tested for face validity and its content validity index ranged from 0.80 to 1.0. The reliability of the instrument was computed and the Cronbach’s alpha was revealed to be .732. Results A total of 33 postgraduate distance learners participated in the survey. The study revealed that about 42.4% of the respondentswere not aware of the guidance and counselling services in the university. One-third (33.3%) of theserespondents agreed that guidance and counsellingweremost needed during the application process. Additionally, reasons related to academicsranked first (mean=1.5758) among the students’ perceived need for the service to address theirissues. Moreover, one-third (33.3%) of the respondents viewed the lack of student awareness of such service as the main challenge in terms of guidance and counselling. Conclusion It was concluded that there is low awareness of the guidance and counselling services among students. As a result, there were only a few currently availingthem.It is therefore recommended tocreate and increase awareness of the availability of guidance and counselling services. Also, training more counsellors can improve their quality and effectiveness